Efficacy of Aloe Vera Cream for Healing Diabetic Foot Ulcers - Tabinda Aqsa,Muhammad Salman Shafique,Usman Qureshi,Mehwish Changeez,Sarosh Afzal Farooqi,Jahangir Sarwar Khan, Tabinda Aqsa,Muhammad Salman Shafique,Usman Qureshi,Mehwish Changeez,Sarosh Afzal Farooqi,Jahangir Sarwar Khan (Journal of Rawalpindi Medical College, 2019)
Background :To compare the efficacy of aloe vera cream with normal saline dressings for infected diabetic leg ulcers. Methods: In this randomized controlled trial 60 patients with infected ulcers on lower limbs were assigned into 2 groups by random sample collection using lottery method. Patients in Group A received aloe vera dressings and patients in Group B received saline soaked dressings daily and were advised to revisit after 8 days. Wound was assessed on the very first visit and then on the 8th day. Patients were assessed with reference to duration of diabetes, grade of ulcer, body mass index and efficacy of treatment. Results: Out of 60 patients, majority were females (53.33%). The efficacy of AVC (aloe vera) dressing was significantly higher than that of NSD (normal saline dressing). i.e. 100% vs 53.3%. (p-value = 0.000) Similar trend was observed for age, gender, BMI, Grade of ulcer and duration of diabetes (p = < 0.05) except for patients with 11-15 years of diabetes & obesity. Conclusion: Efficacy of Aloe vera is higher as compared to that of NSD for treating diabetic foot ulcers. Added advantage of Aloe vera is its cost effectiveness and minimal side effects.